High Fat Diet Increases Circulating Endocannabinoids Accompanied by Increased Synthesis Enzymes in Adipose Tissue - Kuipers, Eline N.; Kantae, Vasudev; Maarse, Boukje C. Eveleens; van den Berg, Susan M.; van Eenige, Robin; Nahon, Kimberly J.; Reifel-Miller, Anne; Coskun, Tamer; de Winther, Menno P. J.; Lutgens, Esther; Kooijman, Sander; Harms, Amy C.; et al. (Frontiers in Physiology, 2019)
The endocannabinoid system (ECS) controls energy balance by regulating both energy intake and energy expenditure. Endocannabinoid levels are elevated in obesity suggesting a potential causal relationship. This study aimed to elucidate the rate of dysregulation of the ECS, and the metabolic organs involved, in diet-induced obesity. Eight groups of age-matched male C57Bl/6J mice were randomized to receive a chow diet (control) or receive a high fat diet (HFD, 45% of calories derived from fat) ranging from 1 day up to 18 weeks before euthanasia. Plasma levels of the endocannabinoids 2-AG and AEA, and related N-acylethanolamines, were quantified by UPLC-MS/MS and gene expression of components of the ECS was determined in liver, muscle, white adipose tissue (WAT) and brown adipose tissue (BAT) during the course of diet-induced obesity development. HFD feeding gradually increased 2-AG (+132% within 4 weeks, P<0.05), accompanied by upregulated expression of its synthesizing enzymes Daglα and ß in WAT and BAT. HFD also rapidly increased AEA (+81% within 1 week, P<0.01), accompanied by increased expression of its synthesizing enzyme Nape-pld, specifically in BAT. Interestingly, Nape-pld expression in BAT correlated with plasma AEA levels (R2=0.171, β=0.276, P<0.001). We conclude that a HFD rapidly activates adipose tissue depots to increase the synthesis pathways of endocannabinoids that may aggravate the development of HFD-induced obesity.